Clinical and genetic characteristics and medical approach in attenuated form of familial adenomatosis of the colon - A. M. Kuzminov; A. V. Karpukhin; I. Yu. Sachkov; Yu. Yu. Chubarov; T. A. Savel’yeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study clinical and genetic characteristics of the attenuated form of familial adenomatosis of the colon. Material and methods. Overall 123 patients with familial adenomatosis of the colon, underwent clinical and genetic investigation. Results. Of all patients 60,2 % had classical form of disease, 24,4% – aggressive, 15,4% – attenuated. At attenuated form mutation in АРС gene occurred within 450 and 510 codons and on the edges of this gene that allows both to reveal disease at preclinical stage, and to identify the attenuated variant. For this variant of adenomatosis absence of metabolic disorders and development of cancer after 50 years is typical that requires onset of treatment by endoscopic polypectomy with subsequent extensive resections of the colon if necessary.